2007
DOI: 10.1371/journal.pcbi.0030156
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Firing Patterns in Fast-Spiking Cortical Interneurons

Abstract: Cortical fast-spiking (FS) interneurons display highly variable electrophysiological properties. Their spike responses to step currents occur almost immediately following the step onset or after a substantial delay, during which subthreshold oscillations are frequently observed. Their firing patterns include high-frequency tonic firing and rhythmic or irregular bursting (stuttering). What is the origin of this variability? In the present paper, we hypothesize that it emerges naturally if one assumes a continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
123
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(134 citation statements)
references
References 57 publications
11
123
0
Order By: Relevance
“…Irregular motor neuron firing induced by sepsis was closely associated with high frequency (>100 Hz) membrane potential oscillations between spikes (Fig 1). Irregular firing associated with high frequency membrane potential oscillations has been previously described in a variety of neuron types 18, 19 , including mouse motor neurons 14, 20 . In sodium pentobarbitone anesthetized mice, irregular firing and membrane potential oscillations are seen in motor neurons during slow triangular ramps of current injection when current intensity is just suprathreshold 14, 20 .…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Irregular motor neuron firing induced by sepsis was closely associated with high frequency (>100 Hz) membrane potential oscillations between spikes (Fig 1). Irregular firing associated with high frequency membrane potential oscillations has been previously described in a variety of neuron types 18, 19 , including mouse motor neurons 14, 20 . In sodium pentobarbitone anesthetized mice, irregular firing and membrane potential oscillations are seen in motor neurons during slow triangular ramps of current injection when current intensity is just suprathreshold 14, 20 .…”
Section: Resultsmentioning
confidence: 85%
“…Oscillations in membrane potential during firing are thought to reflect the competing influence of inward and outward currents mediated by fast, voltage-dependent currents that are activated in the subthreshold range 14, 1820 . As subthreshold currents serve to drive the motor neuron to action potential threshold, the finding of oscillations suggested that dysregulation of subthreshold currents might be the mechanism underlying the defect in motor neuron repetitive firing induced by sepsis.…”
Section: Resultsmentioning
confidence: 99%
“…Some experiments were also performed with a model neuron that produced tonic discharge ( θ m  = −28 mV, g KD  = 0.39 mS/cm 2 , see Figures A2 and A3 in Appendix). To induce oscillatory fluctuations in the subthreshold membrane potential during the interburst episodes, a Gaussian white noise current with zero mean and 15 pA SD (0.1 ms time step) was applied to the model neuron (Golomb et al, 2007). …”
Section: Methodsmentioning
confidence: 99%
“…Previous work has shown that high variable electrophysiological properties result from the combined activity of different membrane ion channels (Llinas, 1988) and cell morphology (Mainen et al, 1996). Among those ion channels, the voltage gated potassium channel Kv1 family plays an important role in action potential initiation at near threshold potentials and also serves to suppress action potential firing (Coetzee et al, 1999, Golomb et al, 2007). Additionally, Kvβ1 is an auxiliary subunit that forms complexes with the Kv1 family of ion channels leading to fast inactivation of evoked currents in heterozygous expression systems (Pongs et al, 1999).…”
Section: Discussionmentioning
confidence: 99%